2015
DOI: 10.1152/ajprenal.00563.2014
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of hepatic nuclear factor-4α binding to theStim1promoter contributes to high glucose-induced upregulation of STIM1 expression in glomerular mesangial cells

Abstract: Wang Y, Chaudhari S, Ren Y, Ma R. Impairment of hepatic nuclear factor 4␣ binding to the Stim1 promoter contributes to high glucoseinduced upregulation of STIM1 expression in glomerular mesangial cells. Am J Physiol Renal Physiol 308: F1135-F1145, 2015. First published March 18, 2015 doi:10.1152/ajprenal.00563.2014.-The present study was carried out to investigate if hepatic nuclear factor (HNF)4␣ contributed to the high glucose-induced increase in stromal interacting molecule (STIM)1 protein abundance in glo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 59 publications
0
7
1
Order By: Relevance
“…Thus, superoxide might be a common ER stress inducer in different cell types including endothelial cells in diabetes. Interestingly, ER stress inducer such as tunicamycin or thapsigargin induces Orai1 and STIM1 expression in multiple cells and high glucose is related to an increase in Orai1 and STIM1 activity3940. In this present study, we did not see any difference in the expression of Orai1 and STIM1.…”
Section: Discussioncontrasting
confidence: 55%
“…Thus, superoxide might be a common ER stress inducer in different cell types including endothelial cells in diabetes. Interestingly, ER stress inducer such as tunicamycin or thapsigargin induces Orai1 and STIM1 expression in multiple cells and high glucose is related to an increase in Orai1 and STIM1 activity3940. In this present study, we did not see any difference in the expression of Orai1 and STIM1.…”
Section: Discussioncontrasting
confidence: 55%
“…Moreover, blockade of ORAI channels has been shown to prevent the development of renal fibrosis in mice with chronic kidney disease (CKD) 33 . Furthermore, overexpression of ORAI1 has been shown in other kidney-related diabetic disease 34 . Since we observed that crystal internalization switches the mode of Ca 2+ signaling from ROCE to SOCE, we examined the expression of STIM and ORAI and found that both STIM1, STIM2, and ORAI3 channel expression were upregulated following crystal internalization.…”
Section: Discussionmentioning
confidence: 99%
“…While androgen-independent HNF4A actions seem essential for PTECs, androgen-dependent mechanisms of this transcription factor may result in mitochondrial hyperactivity and predispose to oxidative stress. In diabetes, high glucose alters the levels and activity of HNF4A 149,150 . In turn, HNF4A regulates genes altered in PTECs from diabetic patients 151 .…”
Section: Discussionmentioning
confidence: 99%